Homozygosity for the E526V Mutation in Fibrinogen A Alpha-Chain Amyloidosis: The First Report. (23rd June 2015) - Tavares, Isabel; Lobato, Luísa; Matos, Carlos; Santos, Josefina; Moreira, Paul; Saraiva, Maria João; Castro Henriques, António
Abstract : Systemic hereditary amyloidoses are autosomal dominant diseases associated with mutations in genes encoding ten different proteins. The clinical phenotype has implications on therapeutic approach, but it is commonly variable and largely dependent on the type of mutation. Except for rare cases involving gelsolin or transthyretin, patients are heterozygous for the amyloidogenic variants. Here we describe the first patient identified worldwide as homozygous for a nephropathic amyloidosis, involving the fibrinogen variant associated with the fibrinogen alpha-chain E526V (p.Glu545Val) mutation. In 1989, a 44-year-old woman presented with hypertension, hepatosplenomegaly, nephrotic syndrome, and renal failure. She started hemodialysis in 1990 and 6 years later underwent isolated kidney transplantation from a deceased donor. Graft function and clinical status were unremarkable for 16 years, despite progressively increased left ventricular mass on echocardiography. In 2012, 4 months before death, she deteriorated rapidly with severe heart failure, precipitated by Clostridium difficile colitis and urosepsis. Affected family members developed nephropathy, on average, nearly three decades later, which may be explained by the gene dosage effects on the phenotype of E526V (p.Glu545Val) fibrinogen A alpha-chain amyloidosis.